ANALYSIS OF THE ROLE OF MIDWIVES ON THE SELECTION OF IMPLANTED CONTRACEPTIVE USE BY ACCEPTORS: A LITERATURE REVIEW - Polanda Y Runtoboi; Mardiana Ahmad; Andi Nilawati Usman (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Indonesian family profiles reported the percentage of active acceptors in couples of childbearing ages in 2017 was 63.22%, and the number who never used contraceptives was 18.63%. The highest contraceptive use in Bengkulu province was 71.98%, and the lowest in Papua was 25.73%. The population of Papua Province in 2020 amounted to 4.3 million people or an increase of 1.47 million. Objectives: This study aims to find the role of midwives against the selection of the use of implanted contraceptives by acceptors. Design: This research design is a systematic review to find and review articles from databases and theories that are descriptive. Data Sources: Search articles using databased ScienceDirect and Google Scholar including the keyword